Implications of Lantana camara invasion on rural livelihoods and native woody species in the Kavango Zambezi Transfrontier Conservation Area, Zimbabwe - Francis, Buhle (Rhodes University, Faculty of Science, Department of Environmental Science)
Lantana (Lantana camara Linn, Verbenaceae) is an invasive alien species found in many disturbed and conservation habitats worldwide. Much work has been conducted on the impacts that L. camara has on ecosystems and communities living in affected areas. In some localities, interventions to eradicate L. camara have been made to reduce the impacts, with follow-up assessments on the benefits of these restoration efforts at some locations. However, L. camara continues to spread globally, and the Zambezi Transfrontier Conservation Area (KAZA TFCA) in Zimbabwe has not been spared. The KAZA TFCA is an important area for biodiversity conservation, ecotourism, and enabling and encouraging regional peace, cooperation and socio-economic advancement. This study was carried out in the KAZA TFCA, covering the Hwange District in Zimbabwe, with the primary aim to ascertain the effects of L. camara on rural livelihoods, native woody species and the soil properties of KAZA TFCA, and whether the policy environment and passive restoration efforts have been effective in controlling it in the area. The study employed a mixed-methods approach using both qualitative and quantitative methodologies to resolve the research problem. Firstly, 102 plots were randomly established in the study areas where native woody species were recorded. In the first section of the Communal area, there were 60 plots in total comprising of 34 invaded and 8 uninvaded. In the other section of the Communal area, 21 plots were sampled, with 7 invaded, 7 control and the other 7 cleared. In the Victoria Falls National Park, 18 plots were established which comprised of 12 invaded and 6 uninvaded. In the Victoria Falls Rainforest area, 21 plots were established which comprised of 7 invaded, 7 cleared and 7 control. The criteria of selecting 102 plots was based on a number of factors which included; Research objectives, Randomisation, Historical data (From locals and Environmental Management Agency), Environmental variables, Spatial distribution if invasion, Accessibility, Budget and Time constraints. A total of 72 soil samples were collected for laboratory analysis of nitrogen, pH, organic carbon, phosphorous and potassium. The 72 soil samples were considered based on available funding for analysis. This soil samples collected samples were representative of the entire study site. In the Communal areas, 300 household questionnaires (representing approximately 12.35% of the total number of 2 430 households) were administered, two focus groups with elderly residents were conducted, and 11 key informant interviews were held. One-way ANOVAs and several multivariate tests were conducted to assess the impact of L. camara invasion on native woody species composition and soil properties. Descriptive statistics were used to conduct a cost-benefit analysis of the presence of L. camara in the study sites. This was coupled with a principal component analysis to assess vulnerability of respondents to invasion, based on variables such as age, gender and level of education. One-way ANOVAs and multivariate analysis were also used to assess if passive restoration contributed to the recovery of native woody vegetation and the improvement of soil properties. In invaded plots, restoration natural recovery occurred after removing the L. camara invasion with no further intervention done after the removal. Document and thematic analyses were conducted to evaluate perceptions and knowledge of policy and legislation pertaining to L. camara management. Lantana camara negatively affected the native woody species, as evidenced by a reduction in species richness, abundance, density, height and canopy cover. Lantana camara also altered soil properties such as texture, chemical composition, colour and porosity, as found by comparing invaded and non-invaded plots in both the Park and Communal areas. Once L. camara invades an area it tends to become dominant at the expense of native species, many of which are a source of livelihood for the local people. Thus, displacement of native species by L. camara potentially increases the vulnerability of local people, some of whom are already experiencing challenges, such as drought and human-wildlife conflict. The invasion of L. camara was found to date back over eight decades ago. Based on focus group discussions with elderly participants, the initial invasion of L. camara in the Ndlovu Communal area was approximated to 1942. This invasion was noted to have begun in ward 2 of Ndlovu Communal area and spread to the other four wards in the study area over 16 years. Despite the challenges of losses and costs induced by the invasion of L. camara, benefits and gains were reported in some areas. For example, in the protected areas, the fruits of L. camara are eaten by birds, while bees use the flowers for honey production. It is noted that L. camara seeds spread through bird droppings become a cost to the environment through further proliferation of the invasion. In some communal areas, households use L. camara for hedges, herbal medicine, cane for furniture, and as an ornament. The relative losses and gains associated with L. camara are context-specific and are dependent on several factors. In this study, the presence of L. camara resulted in negative impacts that included the reduced area of productive land for crops and grazing. Combined, the mean costs borne were US$ 483 household-1 year-1. Furthermore, the combined mean benefits of L. camara, such as use as live fencing around homesteads and fields, mosquito repellent, fruit, fire kindling and ornaments, protection of fowls from raptors, and the prevention of gully erosion along watercourses, were valued at US$ 716 household-1 year-1, thereby exceeding the costs by 48%. However, most (62%) households experienced a net negative cost-benefit ratio. The overall mean value across the sample indicates benefits outweigh costs because a minority of households experience large net benefits. Although L. camara is invasive in the area, communities have taken advantage of its presence to find uses that contribute to their day-to-day lives. Despite the use of L. camara by communities, efforts to remove it have been made in some parts of the Ndlovu Communal area as well as in the Parks (Victoria Falls and Rainforest). The study investigated the impact of passive restoration on native woody species and soil properties. The findings showed a significant improvement in species richness and diversity in cleared plots compared with invaded plots. The species composition differed in the cleared, invaded and uninvaded plots with specific species favouring the different types of "treatments" . This showed the relationship between invasion and associated species. Soil properties had visible differences due to passive restoration, with figures of cleared sites consistently being intermediates of invaded and uninvaded plots. Despite the passive restoration projects, an analysis of knowledge and management showed that most local respondents whose age ranged between 25- 93 years, did not consider L. camara to be invasive but viewed it as part of the vegetation in the area. They also took little responsibility for its management. A further analysis of documents and policies related to the management of invasive alien species found that there were legal instruments in place for the management of invasive alien plants in Zimbabwe, including L. camara. The key informant interviews and the questionnaire surveys showed conflicting views on perceptions and opinions about whose responsibility it was to manage L. camara, with communities saying it is the authority's responsibility, while some of the authorities suggested that it was everyone's responsibility. However, some of the key informants highlighted the need to review the policies, guided by empirical studies on of the impacts of L. camara. Currently, it appears the policies are adopted from international bodies as a means of alignment to global policies, but they are not contextualised to suit the dynamics in the country. Overall, the study showed that the presence of L. camara in the KAZA TFCA has notable negative impacts on the native woody vegetation, as well as on local livelihoods, but some households have adapted to using L. camara to benefit them. This, however, has implications for efforts to stop the spread of L. camara if its presence is considered a benefit by some and a cost by others. The efforts to remove L. camara show that the native woody vegetation recovered. The study showed the need to raise awareness of the invasive nature of L. camara because some respondents did not consider it invasive. Findings from this study have implications for the management of L. camara in KAZA TFCA and similar areas, and inferences can be made to assist in the management of other invasive alien plants.,Thesis (PhD) -- Faculty of Science, Environmental Science, 2024
Keywords: Invasive plants -- Zimbabwe; Livelihood; Cost-benefit analysis; Commons; Kavango-Zambezi Transfrontier Conservation Area Secretariat; Invasive plants -- Environmental aspects -- Zimbabwe